Single-Atom Electrocatalysts for Lithium Sulfur Batteries: Progress, Opportunities, and Challenges - Wang, Feifei; Li, Jing; Zhao, Juan; Yang, Yixiao; Su, Chenliang; Zhong, Yu Lin; Yang, Quan-Hong; Lu, Jiong (ACS materials letters, 2020)
Lithium sulfur (Li–S) battery is considered as one of the most promising energy storage devices, because of its low cost, high energy density, and environmental friendliness. However, the practical applications of Li–S batteries have been hindered by a low utilization efficiency of sulfur arising from complicated chemical conversion of polysulfides and the corrosion of Li metal electrode during charge/discharge processes. Single atom catalysts (SACs) consisting of atomically-dispersed metal sites have been recently exploited as high-performance electrocatalytic materials in various energy storage devices, including Li–S batteries, because of their unique catalytic properties and maximized atom efficiency. In this mini-review, we first describe the major roadblocks and opportunities for the development of commercial Li–S batteries. Following that, we will highlight the specific roles of SAC materials, which are used as cathodes, separators, interlayers, electrolytes, and anodes in Li–S batteries. The detailed catalytic conversion mechanism of polysulfides and nucleation process of Li ions over single-atom active sites are also discussed. Finally, we highlight major challenges to be addressed in this field and provide our perspectives in the rational design and synthesis of superior SACs to accelerate their application in Li–S batteries.